Impact of Contextual Factors on the Attendance and Role in the Evidence-Based Chronic Disease Prevention Programs Among Primary Care Practitioners in Shanghai, China - Liu, Xin; Gong, Xin; Gao, Xiang; Wang, Zhaoxin; Lu, Sheng; Chen, Chen; Jin, Hua; Chen, Ning; Yang, Yan; Cai, Meiyu; Shi, Jianwei (Frontiers in Public Health, 2022)
Background The implementation of evidence-based approaches by general practitioners (GPs) is new in the primary care setting, and few quantitative studies have evaluated the impact of contextual factors on the attendance of these approaches. Methods In total, 892 GPs from 75 community healthcare centers (CHCs) in Shanghai completed our survey. We used logistic regression to analyze factors affecting the number of evidence-based chronic disease programs attended by GPs and whether they had held the lead position in such a program. Results A total of 346 (38.8%) of the practitioners had never participated in any evidence-based chronic disease prevention (EBCDP) program. The EBCDP interventions in which the GPs had participated were predominantly related to hypertension, diabetes, and cardiovascular disease. However, the proportion of GPs in the lead role was relatively low, between 0.8% (programs involving prevention and control of asthma) and 5.0% (diabetes). Organizational factors and areas were significantly associated with evidence-based practices (EBPs) of the GP, while monthly income and department were the most significantly related to GPs who have the lead role in a program. The results indicated that GPs who had taken the lead position had higher scores for policy and economic impeding factors. GPs who were men, had a higher income, and worked in prevention and healthcare departments and urban areas were more likely to take the lead position. Conclusion Evidence-based programs for chronic diseases should be extended to different types of diseases. Personal, organizational, political, and economic factors and the factors of female sex, lower income, department type, and suburban area environment should be considered to facilitate the translation of evidence to practice.